KONSUMSI OKSIGEN BENIH IKAN KERAPU BEBEK (Cromileptes altivelis) UKURAN PANJANG 5-7 CM - Yopi Novita; Budhi Hascaryo Iskandar; Bambang Murdiyanto; Budy Wiryawan; Hariyanto Hariyanto (Bogor Agricultural University, 2011)
Disolved oxygen plays an important role for fish living in its life environment. Information on the ammount of oxygen consumption of a fish in certain volume of water is needed in order to give balancing between the ammount of disolved oxygen and fish in it. The objective of this research is obtaining oxygen consumption level of a juvenile of humpback grouper (Cromileptes altivelis) of 5-7 cm body length. Oxygen consumption of fish was measured using a tube that equiped with DO tool (dissolved oxygent, DO), and the tube was filled by sea water. Measurement of oxygen con-sumption of juvenil was done by measuring the concentration of dissolved oxygen from sea water in the respirometer tube, began when fish had entered into the respirometer tube up to two hours observation. The result showed that oxygen consumption rate of a juvenile of humpback grouper (Cromileptes altivelis) of 5-7 cm length, is ranging between 0.816 and 1.734 mg/hour.